PENGARUH KREATIVITAS GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 1 AMANUBAN TENGAH - Abor, Semuel Kristofel; Yewang, Markus U.K; Loe, Andri Paulus (Journal Economic Education, Business and Accounting, 2024)
The low learning outcomes of SMA Negeri 1 Amanuban Tengah students in economics subjects was the impetus for conducting this research. The aim of this research is to determine the influence of teacher creativity on student learning outcomes, the influence of learning motivation on student learning outcomes, and the influence of teacher creativity and learning motivation simultaneously on student learning outcomes at SMA Negeri 1 Amanuban Tengah. This research uses quantitative methodology. The research sample consisted of 98 social studies students from class X IPS. Applying multiple linear regression analysis methods. SPSS 25 was used for research testing. Results from research: (1) teacher creativity has a positive and significant effect on learning outcomes, indicated by a significance value of 0.000 < probability (0.05) and tvalue (182.273) > ttable (1.661). (2) The results of tvalue (4.029) > ttable (1.661) and significance value (0.000) < probability (0.05) indicate that learning motivation has a good and significant effect on learning outcomes. (3) Learning motivation and teacher creativity together have a positive and significant effect on student learning outcomes, as evidenced by the significance value (0.000) < probability (0.05) and the Fvalue (40.097) > Ftable (3.092). Keywords: Teacher Creativity, Learning Motivation, Learning Results